Menstrual Disorder Affects Academic Stress on Students - Jehan Puspasari; Veronica Yeni Rahmawati; Dian Fitria (Poltekkes Kemenkes Yogyakarta, 2022)
Adolescence is a period of development towards adulthood with all the changes that occur both physiologically and psychologically. In adolescent girls physiologically will experience menstruation. Adolescents have a tendency to experience menstrual disorders, and one of the factors is academic stress. This research used cross sectional method with total sampling. The results of univariate analysis showed that the average age of menarche was 12 years, the average BMI was 20.50, good nutritional status was 66.7%, students did not experience menstrual disorders by 84.4% and the academic stress level of students was 80.9%. The results of the bivariate analysis showed a correlation coefficient of 0.635, with a p-value of 0.001 which means the higher the menstrual disorder, the higher the academic stress on students. These findings can be used to develop health promotion related to reproductive health in adolescent girls so as to reduce stress levels in students.